Why is the VAT Not a ‘Money Machine’ in Sri Lanka? - Amirthalingam, Kopalapillai (Sri Lanka Economic Journal, 2010)
Value Added Tax (VAT) has proved itself an effective form of taxation and its growth is unprecedented by any other concept in taxation in the world. As in most other developed and developing countries the push for fundamental tax reform has grown out of frustration over the inefficiency, inequity, and complexity of the existing tax system in Sri Lanka too. Though Sri Lanka introduced VAT with a view to generating greater revenue, the performance of the Sri Lankan VAT contrasts sharply with its reputation as a ‘money machine’. The VAT may not be an ideal tax and money machine for Sri Lanka until the four circumstances-(a) small-scale agriculture is important, (b) retail trade is fragmented among very small sellers, (c) basic accounting is not widespread, and (d) efficient and impartial tax administration has not been achieved - disappear as a result of economic change or are resolved by the tax authority.
Keywords: Value added tax; Indirect tax; Sri Lanka